Globicephala melas - Russell A. Mittermeier; Don E. Wilson (Lynx Edicions, 2014)
25. Long-finned Pilot Whale Globicephala melas French: Globicéphale noir / German: Langflossen-Grindwal / Spanish: Calderén de aleta larga Other common names: Atlantic Pilot Whale, Caaing Whale, Common Blackfish, Common Pilot Whale, Northern Pilot Whale, Pothead Whale; North Atlantic Long-finned Pilot Whale (melas); Southern Long-finned Pilot Whale (edward) Taxonomy. Delphinus melas Traill, 1809, “in Scapay Bay, in Pomona, one of the Orkneys,” Scotland, UK. Taxonomy of G. melas is currently in dispute. It currently consists of two subspecies, a northern form (melas) and a southern form (edwardii), but full species status has also been argued for these taxa. There is also some morphological evidence that the northern form itself may consist of two forms, north-eastern and north-western, which are geographically segregated by gyre currents of the North Atlantic Ocean. Skulls from Japan indicate that a subspecies (as yet unnamed) existed in north-western Pacific Ocean from the 8" to the 12" centuries. Two subspecies recognized. Subspecies and Distribution. G.m.melasTraill,1809—NAtlanticOceannofartherSthanapproximatelytheTropicofCancer,includingtheBarentsSea,WMediterraneanSea,NorthSea,andGulfofSaintLawrence. G. m. edwardii Smith, 1834 — circumglobal in the Southern Ocean from 14° S to 68° S. Descriptive notes. Total length 670 cm (males) and 570 cm (females); weight 2300 kg (males) and 1300 kg (females). Neonates are 170-180 cm long and weigh c.75 kg. Like the Short-finned Pilot Whale (G. macrorhynchus), the Long-finned Pilot Whale has bulbous head; slight, barely visible beak; and deep tailstock. Key feature that distinguishes it from the Short-finned Pilot Whale (and the source of its common name) is pair of very long flippers (18-27% of total body length) that curve to form a pronounced “elbow.” Dorsal fin is falcate, with wide base, and is positioned one-third of body length back from snout. Skin pigmentation ranges from a dark gray or brown to black, with several white or pale-gray patches. These include chest ...